Yedoma Cryostratigraphy of Recently Excavated Sections of the CRREL Permafrost Tunnel Near Fairbanks, Alaska - Kanevskiy, Mikhail; Shur, Yuri; Bigelow, Nancy H.; Bjella, Kevin L.; Douglas, Thomas A.; Fortier, Daniel; Jones, Benjamin M.; Jorgenson, M. Torre (Frontiers in Earth Science, 2022)
The new CRREL permafrost tunnel provides a unique opportunity to study properties of Yedoma – late Pleistocene ice- and organic-rich syngenetic permafrost. Yedoma has been described at numerous sites across Interior Alaska, mainly within the Yukon-Tanana upland. The most comprehensive data on the structure and properties of Yedoma in this area have been obtained in the CRREL Permafrost Tunnel near Fairbanks, which became available to researchers in the mid-1960s. Expansion of the new ~4-m-high and ~4-m-wide linear excavations, started in 2011 and ongoing, exposes well-preserved Yedoma and provides access to sediments deposited over the past 40,000 years to scientists interested in paleoecology and studies of the structure, biogeochemical characteristics, and deposition history of this ice-rich permafrost. In this paper, we present results of detailed cryostratigraphic studies in the Tunnel and adjacent area. Data from our study include ground-ice content, the stable water isotope composition of the variety of ground-ice bodies, and radiocarbon dates. Based on cryostratigraphic mapping of the Tunnel and results of drilling, six main cryostratigraphic units have been distinguished: (1) active layer; (2) modern intermediate layer (ice-rich silt); (3) relatively ice-poor Yedoma silt reworked by thermal erosion and thermokarst during the Holocene; (4) ice-rich late Pleistocene Yedoma silt with large ice wedges; (5) relatively ice-poor fluvial gravel; and (6) ice-poor bedrock. Our studies reveal significant differences in cryostratigraphy of the new and old CRREL Permafrost Tunnel facilities. Original syngenetic permafrost in the new Tunnel has been better preserved and less affected by erosional events during the period of Yedoma formation, although numerous features (e.g., bodies of thermokarst-cave ice, thaw unconformities, buried gullies) indicate that the original Yedoma silt in the recently excavated sections was also reworked to some extent by thermokarst and thermal erosion during the Pleistocene and Holocene.